The Impact of an Appraisal System on Employees Performance in Ghana: A Study of the Ministry of Food and Agriculture - Prah, D. (University of Ghana, 2019)
The aim of the study is to examine the impact of performance appraisal system on employee’s performance, at the Ministry of Food and Agriculture (MoFA). The study adopted the descriptive survey design and employed the quantitative research approach. The population of the study was staff at the Ministry of Food and Agriculture. Convenience sampling technique was used to select the respondents. The study used questionnaire to collect data from the respondents. Data processing was done by Statistical Package for Social Sciences (SPSS) and descriptive statistics including mean, standard deviation and rank score. The study found that performance appraisal provided the scope for expressions on developmental needs; and appraisal impacts by helping employees to better understand their job, skills, and a platform for self-reflection. The study also revealed that the performance appraisal tool used was clearly understood and created a participative environment in which employees were informed in advance of when to be evaluated. The study found that performance appraisal system provides an opportunity for supportive superior-subordinate communication to facilitate job performance. Additionally, the finding revealed that the appraisal system used was practical in terms of clarification of information regarding expectations and standards. Some performance appraisal activities are opposed by employees in a bid to protect their jobs. This study recommends that each employee should be allowed to participate in periodic sessions to review performance and clarify expectations. Both the supervisor and the employee should recognize these sessions as constructive occasions for two-way communication.
MA.
Keywords: Appraisal System; Ministry of Food and Agriculture